Body mass and weight thresholds for increased prosthetic joint infection rates after primary total joint arthroplasty. (3rd March 2016) - Lübbeke, Anne; Zingg, Matthieu; Vu, Diemlan; Miozzari, Hermes H; Christofilopoulos, Panayiotis; Uçkay, Ilker; Harbarth, Stephan; Hoffmeyer, Pierre
Abstract : Background and purpose — Obesity increases the risk of deep infection after total joint arthroplasty (TJA). Our objective was to determine whether there may be body mass index (BMI) and weight thresholds indicating a higher prosthetic joint infection rate. Patients and methods — We included all 9, 061 primary hip and knee arthroplasties (mean age 70 years, 61% women) performed between March 1996 and December 2013 where the patient had received intravenous cefuroxime (1.5 g) perioperatively. The main exposures of interest were BMI (5 categories: < 24.9, 25–29.9, 30–34.9, 35–39.9, and ≥ 40) and weight (5 categories: < 60, 60–79, 80–99, 100–119, and ≥ 120 kg). Numbers of TJAs according to BMI categories (lowest to highest) were as follows: 2, 956, 3, 350, 1, 908, 633, and 214, respectively. The main outcome was prosthetic joint infection. The mean follow-up time was 6.5 years (0.5–18 years). Results — 111 prosthetic joint infections were observed: 68 postoperative, 16 hematogenous, and 27 of undetermined cause. Incidence rates were similar in the first 3 BMI categories (< 35), but they were twice as high with BMI 35–39.9 (adjusted HR = 2.1, 95% CI: 1.1–4.3) and 4 times higher with BMI ≥ 40 (adjusted HR = 4.2, 95% CI: 1.8–9.7). Weight ≥ 100 kg was identified as threshold for a significant increase in infection from the early postoperative period onward (adjusted HR = 2.1, 95% CI: 1.3–3.6). Interpretation — BMI ≥ 35 or weight ≥ 100 kg may serve as a cutoff for higher perioperative dosage of antibiotics.